Effect of Sodium Aluminate Dosage as a Solid Alkaline Activator on the Properties of Alkali-Activated Slag Paste - Bin Chen; Jun Wang; Jinyou Zhao (Advances in Materials Science and Engineering)
Extensive research into alkali-activated slag as a green gel material to substitute for cement has been done because of the advantages of low-carbon dioxide emissions and recycling of industrial solid waste. Alkali-activated slag usually has good mechanical properties, but the too fast setting time restricted its application and promotion. Changing the composition of alkaline activator could optimize setting time, usually making it by adding sodium carbonate or sodium sulfate but this would cause insufficient hydration reaction power and hinder compressive strength growth. In this paper, the effect of sodium aluminate dosage as an alkaline activator on the setting time, fluidity, compressive strength, hydration products, and microstructures was studied through experiments. It is fair to say that an appropriate amount of sodium aluminate could obtain a suitable setting time and better compressive strength. Sodium aluminate provided enough hydroxyl ions for the paste to promote the hydration reaction process that ensured obtaining high compressive strength and soluble aluminium formed precipitate wrapped on the surface of slag to inhibit the hydration reaction process in the early phase that prolonged setting time. The hydration mechanism research found that sodium aluminate played a key role in the formation of higher cross-linked gel hydration products in the late phase of the process. Preparing an alkali-activated slag with excellent mechanical properties and suitable setting time will significantly contribute to its application and promotion.